INTEGRASI NILAI-NILAI PLURALISME DALAM PEMBELAJARAN PAI DI MTS HIDAYATUL ISLAM TANJUNGHARJO - Habib Fahrur Rozi; Ninik Nurul Hidayah; Salfa Nur Fadilah; Ahmad Manshur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The importance of enhancing pluralistic values ​​in Islamic Religious Education learning in diverse communities is the primary motivation behind this study. In reality, the integration of these values ​​is often implicit and suboptimal. The purpose of this study is to explain the process of incorporating pluralistic values ​​into Islamic Religious Education (PAI) learning in Islamic Junior High Schools (Madrasah Tsanawiyah) and to identify the factors influencing it. This study employed a case study design and qualitative methodology. Data were collected through observation, interviews, and documentation; observation sheets were used as the primary tool. To determine the level of indicator achievement, descriptive methods were used for data analysis, supported by simple statistical analysis. The results indicate that the integration of pluralistic values ​​is more dominant during the implementation stage of learning through discussion methods, contextual approaches, and teacher role models, while at the planning stage it is not yet systematically structured. The conclusion of this study indicates that PAI learning has great potential in internalizing pluralistic values, but requires strengthening in aspects of planning, methods, and policy support. The implications of this research emphasize the importance of developing more inclusive and contextual learning in the madrasah environment.